3(z-4)-1=4(z-5)

Simple and best practice solution for 3(z-4)-1=4(z-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(z-4)-1=4(z-5) equation:


Simplifying
3(z + -4) + -1 = 4(z + -5)

Reorder the terms:
3(-4 + z) + -1 = 4(z + -5)
(-4 * 3 + z * 3) + -1 = 4(z + -5)
(-12 + 3z) + -1 = 4(z + -5)

Reorder the terms:
-12 + -1 + 3z = 4(z + -5)

Combine like terms: -12 + -1 = -13
-13 + 3z = 4(z + -5)

Reorder the terms:
-13 + 3z = 4(-5 + z)
-13 + 3z = (-5 * 4 + z * 4)
-13 + 3z = (-20 + 4z)

Solving
-13 + 3z = -20 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
-13 + 3z + -4z = -20 + 4z + -4z

Combine like terms: 3z + -4z = -1z
-13 + -1z = -20 + 4z + -4z

Combine like terms: 4z + -4z = 0
-13 + -1z = -20 + 0
-13 + -1z = -20

Add '13' to each side of the equation.
-13 + 13 + -1z = -20 + 13

Combine like terms: -13 + 13 = 0
0 + -1z = -20 + 13
-1z = -20 + 13

Combine like terms: -20 + 13 = -7
-1z = -7

Divide each side by '-1'.
z = 7

Simplifying
z = 7

See similar equations:

| x*ln(x)-2=0 | | 2x^2+30x+99=0 | | y^2-2y-104=0 | | 4x^2-23x-35=o | | 12x+13=21 | | 8(x-2)=-6(x+4)+43 | | u+7=-6 | | (-5a^6-7)-(-14a^6)= | | x=100+-3x | | Y^3-7y^2=8 | | 32+4x=4(-x+7)-44 | | -2+v=3 | | 9x-88=2x-11 | | Y/3-12=8 | | 4[3+2(x+5)]=76 | | 29+8(q-11)=-12 | | 5x-1(-7x+9)=15 | | (4w^2-15)-(-15w^2)= | | 0.75m-0.5=2+0.25m | | 0.71m-0.5=2+0.25m | | 3x-54=-2 | | 6x+3y=190 | | f(x)=-2senx | | 18x-(4x-2)=142 | | 4d=-8+3d | | D-9.8=-3.2 | | 6x^3+19x^2+15x-28=0 | | D-9.8=3.2 | | 1.2(x)=9.9-1.2(x) | | 2x+(-10)=-2 | | 6p=5p+6 | | 80+-8k=2k |

Equations solver categories